Preparation method and application of manganese-cobalt-doped cerium dioxide nanorod

Through one-step hydrothermal synthesis method, the use of template agents is avoided, and a regular manganese-cobalt-doped ceria nanorod was prepared, which solved the problems of pollution and unsafe operation in the existing technology, and achieved green and environmentally friendly Industrial production and good catalytic performance.

CN119430264APending Publication Date: 2025-02-14HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411524526.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing preparation methods of ceria nanomaterials, template agents are often used to cause wastewater and waste gas pollution, and the preparation conditions are complex, operation is unsafe, and it is difficult to achieve green and environmentally friendly industrial production.

Method used

By adjusting the types and proportions of metal salts and alkaline precipitants, optimizing the hydrothermal conditions, avoiding the use of template agents, and directly performing hydrothermal treatment in distilled water, to prepare a regular morphology manganese and cobalt doped Ceria nanorods.

Benefits of technology

It realizes a manganese-cobalt-doped ceria nanorod with simple preparation conditions, safe operation and environmental protection, and has good catalytic oxidation reaction performance and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430264A_ABST
    Figure CN119430264A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano material preparation, and particularly discloses a preparation method of a manganese-cobalt-doped cerium dioxide nanorod, which comprises the following specific steps: 1) dissolving cerium salt, manganese salt and cobalt salt in distilled water to obtain a solution A; 2) dissolving an alkaline precipitator in distilled water to obtain a solution B; 3) dropwise adding the solution A into the solution B under sufficient stirring, and then transferring the mixed solution into a hydrothermal synthesis kettle for sealing; and 4) after the reaction is finished, cooling, washing and drying, and then roasting at high temperature in an air atmosphere to obtain the manganese-cobalt doped cerium dioxide nanorod material. The preparation method comprises the following steps: preparing a precursor of a manganese-cobalt-cerium composite oxide through a one-step hydrothermal synthesis method by modulating the types of a cerium salt, a manganese salt, a cobalt salt and an alkaline precipitator, and then washing, drying and roasting to obtain the manganese-cobalt-doped cerium dioxide nanorod with a regular morphology and a cubic fluorite structure. The method disclosed by the invention is simple in preparation condition, high in operation safety, green and environment-friendly, and convenient for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material preparation, and relates to the preparation of cerium dioxide composite oxides, and particularly to a method for preparing manganese-cobalt doped cerium dioxide nanorods and application of the prepared manganese-cobalt doped cerium dioxide nanorods in the catalytic oxidation reaction of nitrogen monoxide. Background Art

[0002] Cerium dioxide has a cubic fluorite structure. The octahedral voids in its structure are conducive to the rapid diffusion of ions. It also has two variable oxidation states, showing excellent ability to store and release oxygen. Therefore, it has good application prospects in many fields such as catalysts, electrochemistry, and luminescent materials. At present, the reported cerium dioxide mainly includes nanorods, nanowires, nanocubes, nanotubes, and stacked composite structures. It is well known that the crystal structure, particle morphology, and size of nanomaterials have an important influence on their performance. At the same time, without changing the crystal structure of cerium dioxide, the various properties of cerium dioxide can be further improved by doping with other elements.

[0003] The main methods for preparing cerium dioxide include precipitation method, sol-gel method, hydrothermal method and solvothermal method, among which the hydrothermal method has mild reaction conditions and high operability. In order to obtain nanomaterials with different morphologies, surfactants such as hexadecyltrimethylammonium bromide (CTAB), polyvinylpyrrolidone (PVP), polyethylene glycol (PEG), oleylamine, etc. are generally added as templates or structure-directing agents during the hydrothermal synthesis process. Therefore, wastewater and waste gas containing these organic substances are inevitably generated during the washing, drying and roasting of the materials, which will pollute the environment if not handled properly. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing manganese-cobalt-doped cerium dioxide nanorods. The present invention adopts a simple one-step hydrothermal synthesis method, uses deionized water as a solvent, does not use a template agent, adjusts metal salts, alkaline precipitants, and optimizes hydrothermal conditions to first prepare a precursor of a manganese-cobalt-cerium composite oxide, and then obtains manganese-cobalt-doped cerium dioxide nanorods with a regular morphology and a cubic fluorite structure after washing, drying, and roasting. The preparation conditions of the method of the present invention are simple and mild, the operation safety is high, and it is green and environmentally friendly, and is convenient for industrial production.

[0005] The present invention is achieved through the following technical solutions: A method for preparing manganese-cobalt doped cerium dioxide nanorods comprises the following steps: 1) Add a certain amount of metal salt into distilled water and obtain solution A by magnetic stirring; 2) Add a certain amount of alkaline precipitant into distilled water and obtain solution B by magnetic stirring; 3) Add solution A dropwise into solution B under sufficient stirring, continue stirring for 30-60 min, then transfer the mixture to a hydrothermal synthesis reactor, seal it, and place it in a thermostat at 80-160°C for 6-24 hours; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, and the reactants are washed, dried, and then calcined at high temperature in an air atmosphere to obtain manganese-cobalt doped cerium dioxide nanorods.

[0006] The molar ratio of the cerium salt, the manganese salt and the cobalt salt is 1:0-0.5:0-0.5.

[0007] A further improvement of the present invention is: In the step 1), the cerium salt is cerium nitrate hexahydrate or cerium chloride heptahydrate or a mixture of the two.

[0008] Furthermore, in step 1), the manganese salt is manganese nitrate or manganese chloride tetrahydrate or a mixture of the two.

[0009] Furthermore, in step 1), the cobalt salt is cobalt nitrate hexahydrate or cobalt chloride hexahydrate or a mixture of the two.

[0010] Furthermore, in the step 2), the alkaline precipitant is one or a mixture of two or more of sodium hydroxide, potassium hydroxide and sodium carbonate.

[0011] Furthermore, in the step 2), the molar ratio of the alkaline precipitant to the metal ion is 1-5.

[0012] Furthermore, in step 3), the stirring speed is 500-1000 r / min, and the dropping speed of solution B is controlled to be 1-10 mL / min.

[0013] Furthermore, in the step 3), the inner lining of the hydrothermal synthesis reactor is polytetrafluoroethylene, and the solution filling ratio is 60-80%.

[0014] Furthermore, the drying in step 4) is performed in a forced air drying oven at a drying temperature of 100° C. for a drying time of 12 h.

[0015] Furthermore, the calcination in step 4) is carried out in a muffle furnace, the calcination temperature is 400-600° C., and the calcination time is 4-6 h.

[0016] A further improvement of the present invention is: The application of the manganese-cobalt doped cerium dioxide nanorods prepared by the above method in the catalytic oxidation reaction of nitrogen monoxide.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts cerium salt, manganese salt and cobalt salt to mix and dissolve in distilled water, then add strong alkaline solution as precipitant, stir evenly and transfer to hydrothermal kettle for hydrothermal treatment, so as to control the morphology of the material. In the hydrothermal synthesis process of the present invention, no template or structure directing agent is needed, and distilled water is used as solvent, and the types of metal salt and alkaline precipitant are adjusted, and the hydrothermal conditions are controlled to obtain manganese-cobalt doped cerium dioxide nanorods with uniform and regular morphology and cubic fluorite structure.

[0018] According to literature reports (J. Phys. Chem. B, 2005, 109: 24380; J. Phys. Chem. C, 2008, 112: 17076), a certain concentration of sodium hydroxide and appropriate hydrothermal treatment conditions make the Ce(OH)3 precursor dissolve and recrystallize during the treatment process, and finally cerium dioxide nanorods can be obtained. In the present invention, sodium hydroxide or potassium hydroxide is used to hydrothermally treat the precursor of manganese-cobalt-cerium composite oxide. The results show that a certain amount of manganese and cobalt does not change the crystal structure of cerium dioxide, and manganese-cobalt-cerium ternary composite oxide nanorods are successfully prepared. The preparation method of the present invention is simple, has high operational safety, is low in cost, and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a transmission electron microscope image of the manganese-cobalt doped cerium dioxide nanorods prepared in Example 8 of the present invention.

[0020] Figure 2 This is the X-ray diffraction pattern of the manganese-cobalt doped cerium dioxide nanorods prepared in Example 8 of the present invention.

[0021] Figure 3 The catalytic NO oxidation reaction performance of the manganese and cobalt doped cerium dioxide nanorods prepared in Example 8 of the present invention.

[0022] Figure 4 This is a transmission electron microscopy image of manganese-cobalt doped cerium dioxide prepared in Comparative Example 1 of the present invention.

[0023] Figure 5 This is the X-ray diffraction pattern of manganese-cobalt doped cerium dioxide prepared in Comparative Example 1 of the present invention.

[0024] Figure 6 The NO oxidation reaction performance of the manganese-cobalt doped cerium dioxide prepared in Comparative Example 1 of the present invention.

[0025] Figure 7 This is a transmission electron microscopy image of manganese-cobalt doped cerium dioxide prepared in Comparative Example 2 of the present invention.

[0026] Figure 8 This is the X-ray diffraction pattern of manganese-cobalt doped cerium dioxide prepared in Comparative Example 2 of the present invention.

[0027] Fig. 9 The NO oxidation reaction performance of the manganese-cobalt doped cerium dioxide prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0028] The present invention is described in detail below in conjunction with specific embodiments. Example 1

[0029] 1) Add 2.26 g of cerium chloride heptahydrate, 0.40 g of manganese chloride tetrahydrate, and 0.48 g of cobalt chloride hexahydrate into 40 mL of distilled water and stir to obtain solution A; 2) Add 5.6 g of sodium hydroxide to 20 mL of distilled water and stir magnetically to obtain solution B; 3) Under sufficient stirring, control the drop rate of solution A to 2 mL / min, add it to solution B, continue stirring at a speed of 500 r / min for 30 min, then transfer the mixed solution to a hydrothermal synthesis reactor, seal it, and place it in a 150°C oven for 24 h; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, washed with distilled water and ethanol, dried at 100°C for 12 h, and then calcined in a muffle furnace at 400°C for 5 h under air atmosphere to obtain manganese-cobalt doped cerium dioxide nanorods. Example 2

[0030] 1) Add 2.26 g of cerium chloride heptahydrate, 0.40 g of manganese chloride tetrahydrate, and 0.48 g of cobalt chloride hexahydrate into 40 mL of distilled water and stir to obtain solution A; 2) Add 7.84 g potassium hydroxide to 20 mL distilled water and stir magnetically to obtain solution B; 3) Under sufficient stirring, control the drop rate of solution A to 2 mL / min, add it to solution B, continue stirring at a speed of 500 r / min for 30 min, then transfer the mixed solution to a hydrothermal synthesis reactor, seal it, and place it in a 100°C oven at a constant temperature for 12 h; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, washed with distilled water and ethanol, dried at 100°C for 12 h, and then calcined in a muffle furnace at 400°C for 5 h under air atmosphere to obtain manganese-cobalt doped cerium dioxide nanorods. Example 3

[0031] 1) Add 2.26 g of cerium chloride heptahydrate, 0.40 g of manganese chloride tetrahydrate, and 0.48 g of cobalt chloride hexahydrate into 40 mL of distilled water and stir to obtain solution A; 2) Add 7.42 g of sodium carbonate to 20 mL of distilled water and stir magnetically to obtain solution B; 3) Under sufficient stirring, control the drop rate of solution A to 2 mL / min, add it to solution B, continue stirring at a speed of 500 r / min for 30 min, then transfer the mixed solution to a hydrothermal synthesis reactor, seal it, and place it in a 100°C oven at a constant temperature for 12 h; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, washed with distilled water and ethanol, dried at 100°C for 12 h, and then calcined in a muffle furnace at 400°C for 5 h under air atmosphere to obtain manganese-cobalt doped cerium dioxide nanorods. Example 4

[0032] 1) Add 1.13 g of cerium chloride heptahydrate, 1.32 g of cerium nitrate hexahydrate, 0.40 g of manganese chloride tetrahydrate, and 0.48 g of cobalt chloride hexahydrate into 40 mL of distilled water and stir to obtain solution A; 2) Add 5.6 g of sodium hydroxide to 20 mL of distilled water and stir magnetically to obtain solution B; 3) Under sufficient stirring, control the drop rate of solution A to 2 mL / min, add it to solution B, continue stirring at a speed of 500 r / min for 30 min, then transfer the mixed solution to a hydrothermal synthesis reactor, seal it, and place it in a 90°C oven at a constant temperature for 12 h; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, washed with distilled water and ethanol, dried at 100°C for 12 h, and then calcined in a muffle furnace at 400°C for 5 h under air atmosphere to obtain manganese-cobalt doped cerium dioxide nanorods. Example 5

[0033] 1) Add 2.64 g of cerium nitrate hexahydrate, 0.36 g of manganese nitrate, and 0.59 g of cobalt nitrate hexahydrate into 40 mL of distilled water and stir to obtain solution A; 2) Add 5.6 g of sodium hydroxide to 20 mL of distilled water and stir magnetically to obtain solution B; 3) Under sufficient stirring, control the drop rate of solution A to 2 mL / min, add it to solution B, continue stirring at a speed of 500 r / min for 30 min, then transfer the mixed solution to a hydrothermal synthesis reactor, seal it, and place it in a 100°C oven at a constant temperature for 12 h; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, washed with distilled water and ethanol, dried at 100°C for 12 h, and then calcined in a muffle furnace at 400°C for 5 h under air atmosphere to obtain manganese-cobalt doped cerium dioxide nanorods. Example 6

[0034] 1) Add 2.64 g of cerium nitrate hexahydrate, 0.36 g of manganese nitrate, and 0.59 g of cobalt nitrate hexahydrate into 40 mL of distilled water and stir to obtain solution A; 2) Add 7.84 g potassium hydroxide to 20 mL distilled water and stir magnetically to obtain solution B; 3) Under sufficient stirring, control the drop rate of solution A to 2 mL / min, add it to solution B, continue stirring at a speed of 500 r / min for 30 min, then transfer the mixed solution to a hydrothermal synthesis reactor, seal it, and place it in a 120°C oven at a constant temperature for 24 h; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, washed with distilled water and ethanol, dried at 100°C for 12 h, and then calcined in a muffle furnace at 400°C for 5 h under air atmosphere to obtain manganese-cobalt doped cerium dioxide nanorods. Example 7

[0035] 1) Add 1.32 g of cerium nitrate hexahydrate, 1.13 g of cerium chloride heptahydrate, 0.36 g of manganese nitrate, and 0.59 g of cobalt nitrate hexahydrate into 40 mL of distilled water and stir to obtain solution A; 2) Add 5.6 g of sodium hydroxide to 20 mL of distilled water and stir magnetically to obtain solution B; 3) Under sufficient stirring, control the drop rate of solution A to 2 mL / min, add it to solution B, continue stirring at a speed of 500 r / min for 30 min, then transfer the mixed solution to a hydrothermal synthesis reactor, seal it, and place it in a 120°C oven at a constant temperature for 24 h; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, washed with distilled water and ethanol, dried at 100°C for 12 h, and then calcined in a muffle furnace at 400°C for 5 h under air atmosphere to obtain manganese-cobalt doped cerium dioxide nanorods. Example 8

[0036] 1) Add 1.32 g of cerium nitrate hexahydrate, 1.13 g of cerium chloride heptahydrate, 0.36 g of manganese nitrate, and 0.59 g of cobalt nitrate hexahydrate into 40 mL of distilled water and stir to obtain solution A; 2) Add 7.84 g potassium hydroxide to 20 mL distilled water and stir magnetically to obtain solution B; 3) Under sufficient stirring, control the drop rate of solution A to 2 mL / min, add it to solution B, continue stirring at a speed of 800 r / min for 60 min, then transfer the mixed solution to a hydrothermal synthesis reactor, seal it, and place it in a 120°C oven for 24 h; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, washed with distilled water and ethanol, dried at 100°C for 12 h, and then calcined in a muffle furnace at 400°C for 5 h under air atmosphere to obtain manganese-cobalt doped cerium dioxide nanorods.

[0037] The transmission electron microscope image of the manganese-cobalt doped cerium dioxide nanorods prepared in Example 8 of the present invention is as follows: Figure 1 As shown, it can be seen that the obtained material is a regular rod-like structure, the length of which is mostly between 50 and 150 nm, and the cross-sectional diameter of the nanorods is about 6-10 nm.

[0038] The X-ray diffraction pattern of the manganese-cobalt doped cerium dioxide nanorods prepared in Example 8 of the present invention is as follows: Figure 2 As shown, it can be seen that all the diffraction peaks correspond to cerium dioxide with a cubic fluorite structure, and the standard spectrum is PDF#43-1002. No diffraction peaks of any other substances appear, indicating that the manganese-cobalt doped cerium dioxide nanorods have a single crystal structure.

[0039] The manganese-cobalt-doped cerium dioxide nanorods prepared in Example 8 were used for the catalytic oxidation reaction of nitric oxide. The specific reaction conditions were: 120 mg catalyst, gas flow rate 100 mL / min, 1000 ppm NO, 3% O2, N2 as the balance gas, and NO-NO2-NO x The analyzer (42i-LS, Thermo Scientific) detects the concentration of NO and NO2 in the outlet gas. The reaction performance is as follows Figure 3 As shown in Figure 5, the NO conversion rate is the highest at 595 K, which is about 71%.

[0040] The present invention does not use surfactants, and by adjusting metal salts, alkaline precipitants, and optimizing hydrothermal reaction conditions, a manganese-cobalt-doped cerium dioxide nanorod with a regular morphology of cubic fluorite structure is prepared through a one-step hydrothermal synthesis method. The method of the present invention has simple preparation conditions, high operational safety, is green and environmentally friendly, and is convenient for industrial production.

[0041] Comparative Example 1 1) Add 2.64 g of cerium nitrate hexahydrate, 0.54 g of manganese nitrate, and 0.59 g of cobalt nitrate hexahydrate into 40 mL of distilled water and stir to obtain solution A; 2) Add 7.84 g potassium hydroxide to 20 mL distilled water and stir magnetically to obtain solution B; 3) Under sufficient stirring, control the drop rate of solution A to 2 mL / min, add it to solution B, continue stirring at a speed of 500 r / min for 30 min, then transfer the mixed solution to a hydrothermal synthesis reactor, seal it, and place it in a 90°C oven at a constant temperature for 12 h; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, washed with distilled water and ethanol, dried at 100°C for 12 h, and then calcined in a muffle furnace at 400°C for 5 h under air atmosphere to obtain manganese-cobalt-cerium composite oxide ( Figure 4 ).

[0042] The electron microscope image of the manganese-cobalt doped cerium dioxide prepared in Comparative Example 1 is as follows: Figure 4 As shown, the morphology of the prepared manganese, cobalt, cerium ternary composite oxide is relatively irregular, mainly nanorods with a length of about 30-50 nm, accompanied by a large number of particles piled together.

[0043] The X-ray diffraction pattern of the sample is shown in Figure 5 As shown, it can be seen that all the diffraction peaks correspond to cerium dioxide with a cubic fluorite structure, and the standard spectrum is PDF#43-1002. No diffraction peaks of any other substances appear, indicating that the manganese-cobalt doped cerium dioxide has a single crystal structure.

[0044] The material is used for the catalytic oxidation reaction of nitric oxide, and the reaction performance is as follows Figure 6 As shown in Figure 5, the NO conversion rate is the highest at 595 K, which is about 60%.

[0045] Comparative Example 2 1) Add 2.26 g of cerium chloride heptahydrate, 0.40 g of manganese chloride tetrahydrate, and 0.48 g of cobalt chloride hexahydrate into 40 mL of distilled water and stir to obtain solution A; 2) Add 5.6 g of sodium hydroxide to 20 mL of distilled water and stir magnetically to obtain solution B; 3) Under sufficient stirring, control the drop rate of solution A to 2 mL / min, add it to solution B, continue stirring at a speed of 500 r / min for 30 min, then transfer the mixed solution to a hydrothermal synthesis reactor, seal it, and place it in a 180°C oven for 24 h; 4) After the reaction is completed, the mixture is naturally cooled to room temperature, washed with distilled water and ethanol, dried at 100°C for 12 h, and then calcined in a muffle furnace at 400°C for 5 h under air atmosphere to obtain manganese-cobalt-cerium composite oxide ( Figure 7 ).

[0046] The electron microscope image of the manganese-cobalt-cerium composite oxide prepared in this comparative example is as follows: Figure 7 As shown in the figure, its morphology is extremely irregular, some rods are longer than 6 μm, and there are a large number of particles piled together, as well as a certain number of cubes.

[0047] The X-ray diffraction pattern of the sample is shown in Figure 8As shown, it can be seen that the main diffraction peak corresponds to the cubic fluorite structure of ceria, and the diffraction peak of MnO2 (111) crystal plane also appears (PDF#44-0992), indicating that some manganese ions have not entered the crystal structure of ceria, or the manganese dioxide particles are relatively large.

[0048] The material is used for the catalytic oxidation reaction of nitric oxide, and the reaction performance is as follows Fig. 9 As shown in Figure 2, the conversion rate of NO is the lowest at 595 K, which is about 47%. This is because the manganese-cobalt-cerium composite oxide has a high degree of crystallinity under high-temperature hydrothermal synthesis conditions (see Figure 8 ), resulting in a decrease in the active surface.

[0049] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing manganese-cobalt doped cerium dioxide nanorods, characterized in that: The following steps are involved: 1) Dissolve a certain amount of cerium salt, manganese salt and cobalt salt in distilled water to obtain solution A; 2) Dissolve a certain amount of alkaline precipitant in distilled water to obtain solution B; 3) Add solution A dropwise into solution B under sufficient stirring, continue stirring for 30-60 min, then transfer the mixture to a hydrothermal synthesis reactor, seal it, and place it in a thermostat at 80-160°C for 6-24 hours; 4) After the reaction is completed, the reaction mixture is naturally cooled to room temperature, and the reactant is washed, dried, and then calcined at high temperature in an air atmosphere to obtain a manganese-cobalt doped cerium dioxide nanorod material; The molar ratio of the cerium salt, the manganese salt and the cobalt salt is 1:0-0.5:0-0.

5.

2. The method for preparing manganese-cobalt-doped cerium dioxide nanorods according to claim 1, characterized in that: In the step 1), the cerium salt is cerium nitrate hexahydrate or cerium chloride heptahydrate or a mixture of the two.

3. The method for preparing manganese-cobalt-doped cerium dioxide nanorods according to claim 1, characterized in that: In the step 1), the manganese salt is manganese nitrate or manganese chloride tetrahydrate or a mixture of the two.

4. The method for preparing manganese-cobalt doped cerium dioxide nanorods according to claim 1, characterized in that: In the step 1), the cobalt salt is cobalt nitrate hexahydrate or cobalt chloride hexahydrate or a mixture of the two.

5. The method for preparing manganese-cobalt doped cerium dioxide nanorods according to claim 1, characterized in that: In the step 2), the alkaline precipitant is one or a mixture of two or more of sodium hydroxide, potassium hydroxide and sodium carbonate.

6. The method for preparing manganese-cobalt doped cerium dioxide nanorods according to claim 1, characterized in that: The molar ratio of the alkaline precipitant to the metal ion is 1-5.

7. The method for preparing manganese-cobalt doped cerium dioxide nanorods according to claim 1, characterized in that: In the step 3), the stirring speed is 500-1000 r / min, and the dropping speed of solution A is controlled to be 1-10 mL / min.

8. The method for preparing manganese-cobalt doped cerium dioxide nanorods according to claim 1, characterized in that: In the step 3), the inner lining of the hydrothermal synthesis reactor is polytetrafluoroethylene, and the solution filling ratio is 60-80%.

9. The method for preparing manganese-cobalt doped cerium dioxide nanorods according to claim 1, characterized in that: The drying in step 4) is completed in a blast drying oven at a drying temperature of 100° C. for a drying time of 12 h; And / or, the calcination is carried out in a muffle furnace, the calcination temperature is 400-600° C., and the calcination time is 4-6 h.

10. Use of the manganese-cobalt doped cerium dioxide nanorod material prepared by the method according to any one of claims 1 to 9 in the catalytic oxidation reaction of nitrogen monoxide.

Citation Information

Cited By

  • Method for generating p-methoxybenzaldehyde through catalytic oxidation and used catalyst

    CN119608179A